Pharmacokinetic and Pharmacodynamic Modeling of Serum Etrolizumab and Circulating β7 Receptor Occupancy in Patients With Ulcerative Colitis. (26th November 2017) - Wei, Xiaohui; Gibiansky, Leonid; Wang, Yehong; Fuh, Franklin; Erickson, Rich; O'Byrne, Sharon; Tang, Meina T.
Abstract: Etrolizumab, a humanized monoclonal antibody, specifically binds to the β7 subunit of the heterodimeric integrins α4β7 and αEβ7. Pharmacokinetic (PK) and pharmacodynamic (PD) data were collected from an etrolizumab phase 1 trial in patients with moderate to severe ulcerative colitis (UC). We developed a mechanism‐based model to simultaneously describe the kinetics of serum etrolizumab concentration and free β7 receptors on circulating intestinal‐homing CD4 + T lymphocytes. Included in the analysis were 38 phase 1 UC patients who received single or 3 monthly doses of etrolizumab intravenously or subcutaneously across a dose range of 0.3 to 10 mg/kg. A quasi–steady‐state target‐mediated drug disposition model was developed to describe the dynamic interaction between serum etrolizumab concentration and free β7 receptors on intestinal‐homing CD4 + T lymphocytes in UC patients. The time profiles of serum etrolizumab and absolute counts of β7 + lymphocytes (expressed as percentage of baseline level) were well described by the quasi–steady‐state target‐mediated drug disposition model. The model was able to characterize the maximum drug occupancy of β7 receptors on intestinal‐homing CD4 + T lymphocytes and the concentration‐dependent duration of occupancy. The 90% effective concentration for etrolizumab to saturate the β7 receptors on intestinal homing CD4 + T cells was 1.3 μg/mL. PK and PD profiles predicted by the model were consistent with observations from a subsequent phase 2 study. In conclusion, an integrated PK/PD model developed in this analysis reasonably described serum etrolizumab PK profiles and the relationship between PK and PD (free β7 receptors on circulating intestinal‐homing CD4 + T lymphocytes) in UC patients.